PERLINDUNGAN HUKUM BAGI PENANAMAN MODAL ASING (PMA) DI INDONESIA - Ria Sintha Devi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
The existence of Foreign Investment in Indonesia is very important and strategic in supporting the implementation of national economic development and increasing economic growth in the community. Foreign investment which is regulated in law No. 25 of 2007 about the legal protection for foreign investment in Indonesia, both investment in the form of a Limited Company (PT) or investment. This shows that foreigners in Indonesia who carry out their capital investment activities are regulated by law and protected by the government under the law. The formulation of the problem were how the position of the establishment of foreign investment companies in Indonesia was, what the procedures for the implementation of foreign investment in Indonesia were, and what efforts have been made by the government if there were violations of law in foreign investment in Indonesia. The results of the study showed every foreign company that wanted to invest in Indonesia had to get the principle permission to the Investment Coordinating Board (BKPM) and the One Stop Integrated Investment and Services Office (PTSP), so that the company could be established in Indonesia and its establishment was in accordance with the procedures of the law on foreign investment so that the foreign investment company was fully under the responsibility and supervision of the Republic of Indonesia. The government also gave relief to foreign investment in Indonesia in freeing the entry tax fees for goods or electronic equipment for foreign investment (PMA) in Indonesia in investing their capital.